2019
DOI: 10.1039/c9ra01251f
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic effects of alfalfa (Medicago sativa) fiber on cecal bacterial composition, short-chain fatty acids, and diarrhea incidence in weaning piglets

Abstract: Dietary alfalfa fiber (AF) is conceived to modulate gut microbial richness and diversity to improve the health and growth of weaning piglets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 71 publications
(112 reference statements)
1
10
0
Order By: Relevance
“…In this study, the addition of alfalfa fiber and commercial fiber significantly improved the growth performance of weaned piglets. This is consistent with the findings of Adams et al (54) and Kroismayr and Roberts (55). Their studies showed that the addition of alfalfa fiber or commercial fiber could increase the ADFI and ADG of piglets.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, the addition of alfalfa fiber and commercial fiber significantly improved the growth performance of weaned piglets. This is consistent with the findings of Adams et al (54) and Kroismayr and Roberts (55). Their studies showed that the addition of alfalfa fiber or commercial fiber could increase the ADFI and ADG of piglets.…”
Section: Discussionsupporting
confidence: 94%
“…From the perspective of the water solubility of the fiber, alfalfa fiber is mainly composed of insoluble dietary fiber such as cellulose, lignin, and xylan, accounting for more than 90% of the total dietary fiber of alfalfa. Similarly, the commercial fiber used in this study is also a kind of insoluble fiber, with a total dietary fiber content of 95%, an insoluble dietary fiber content of 94%, and a lignin content of 30% ( 54 , 56 58 ). The study by Schedle et al ( 59 ) also showed that the addition of insoluble fiber (wheat bran) increased ADFI and ADG of piglets.…”
Section: Discussionmentioning
confidence: 99%
“…The gut commensal Prevotella species mainly contribute to polysaccharide breakdown and short-chain fatty acid production in the gut of weaning piglets [34,35]. The Prevotella 9 genus is one of the dominant species in the gut and is associated with diarrhea incidence in weaning piglets.…”
Section: Discussionmentioning
confidence: 99%
“…The Prevotella 9 genus is one of the dominant species in the gut and is associated with diarrhea incidence in weaning piglets. It has been demonstrated that the supplementation of fiber in the diet of piglets decreased the diarrhea incidence and increased the Prevotella 9 genus abundances [35]. The Prevotella 9 genus abundances in the fecal microbiota of diarrheic piglets were lower than those in non-diarrheic piglets [36].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous shreds of evidence are indicating that the gut microorganisms can directly influence the physiological conditions in human/animals such as improving the host immune system, improving the roles of the intestinal barrier, stimulating the defensive mechanisms against pathogens as well as increasing the defensive mechanisms against inflammatory bowel diseases, producing biological metabolites, regulating autoimmunity, regulating diabetes and preventing obesity, and destroying cancer cells. The host gut–microbiota interactions are dynamic and highly dictated by several environmental conditions particularly diet [ 135 ]. In addition, the gut is reported to have dual and opposing roles of enabling nutrients to enter the body while denying the entry of harmful substances.…”
Section: Physicochemical and Prebiotic Influence Of Dietary Fiber mentioning
confidence: 99%